2017
DOI: 10.1093/icvts/ivw439
|View full text |Cite
|
Sign up to set email alerts
|

National trends and variability in blood utilization in paediatric cardiac surgery

Abstract: We found a discernible variability in the current practice of blood utilization for a given procedure despite variability in the age and complexity of patients, with no changes in practice patterns for the last decade of paediatric cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 14 publications
2
20
0
Order By: Relevance
“…It was found that more RBC units were utilized in the year 2010 than 2005 and 2014 across all Society of Thoracic SurgeonsEuropean Association for Cardio-Thoracic Surgery (STAT) complexity categories. Differences in utilization between 2005 and 2014 could not be demonstrated, suggesting there have been no changes in RBC transfusion practice for that decade of time for the index diagnoses and procedures (4). Neonates and STAT five (most complex) patients received the greatest number of RBC transfusions compared to other ages and STAT categories but no difference was evident among STAT two, three, and four patients (4).…”
Section: Recent Innovations In Perfusion and Cardiopulmonary Bypass Fmentioning
confidence: 97%
See 3 more Smart Citations
“…It was found that more RBC units were utilized in the year 2010 than 2005 and 2014 across all Society of Thoracic SurgeonsEuropean Association for Cardio-Thoracic Surgery (STAT) complexity categories. Differences in utilization between 2005 and 2014 could not be demonstrated, suggesting there have been no changes in RBC transfusion practice for that decade of time for the index diagnoses and procedures (4). Neonates and STAT five (most complex) patients received the greatest number of RBC transfusions compared to other ages and STAT categories but no difference was evident among STAT two, three, and four patients (4).…”
Section: Recent Innovations In Perfusion and Cardiopulmonary Bypass Fmentioning
confidence: 97%
“…Transfusion medicine has improved vastly and the focus has shifted to adverse transfusion reactions such as acute lung injury, immunomodulation, and thrombotic complications (1)(2)(3). With focus increasing on these risks, centers have reevaluated RBC administration algorithms, especially for neonate and infant populations due to having a higher incidence of adverse reactions compared to older pediatric and adult patient populations (1,4). To reduce the potential exposure and risks associated with RBC transfusions, there are practices that can be put in place in the intraoperative period.…”
Section: Recent Innovations In Perfusion and Cardiopulmonary Bypass Fmentioning
confidence: 99%
See 2 more Smart Citations
“…with the most frequently mentioned being low awareness, no funding for set-up cost, education gaps, and stickiness of the old practice (even stronger if combined with the responses for the closely related resistance against change), lack of interdisciplinary commitment, and resistance against change. indicates, that blood utilization is rather driven by culture and behavior than evidence (42,43,(53)(54)(55)).…”
Section: Accelerators and Inhibitors For The Implementation Of Patienmentioning
confidence: 99%